Children with autoimmune hepatitis receiving standard-of-care therapy demonstrate long-term obesity and linear growth delay - Or Steg Saban; Shannon M. Vandriel; Syeda Aiman Fatima; Celine Bourdon; Amrita Mundh; Vicky L. Ng; Simon C. Ling; Robert H.J. Bandsma; Binita M. Kamath (Hepatology Communications)
Background:. Standard-of-care therapy in children with autoimmune hepatitis (AIH) includes induction with prednisone 1–2 mg/kg daily with gradual weaning of the dose. We aimed to test the hypothesis that children with AIH receiving standard-of-care treatment have altered growth trajectories. Methods:. Children diagnosed with AIH between 1997 and 2023 at SickKids had serial growth measurements. Mixed effect models assessed the impact of time and daily steroid exposure on z-scores. Kaplan-Meier survival methods were used to estimate the cumulative incidence of new-onset growth impairments. A time-dependent Cox proportional hazards model was constructed to determine predictors for growth impairments. Results:. Sixty-one children (66% females, median age at diagnosis 11.5 y) were included. BMIz showed a sharp increase, and HAZ declined significantly without returning to baseline. Each 1 mg/kg/d prednisone exposure increased BMIz gain in the first 6 months by 0.27 ([95% CI: 0.11, 0.42], p = 0.001), and decreased HAZ by −0.02 ([95% CI: −0.03, −0.01], p = 0.005). Children diagnosed before puberty exhibited a higher occurrence of excessive weight gain (72.2% vs. 49.3%; log-rank p < 0.01) and obesity (63% vs. 31.5%; log-rank p < 0.01) compared to those diagnosed during puberty. In a Cox proportional-hazards model, young age at diagnosis and daily prednisone dose >10 mg 6 months after diagnosis were predictors for linear growth delay. Conclusions:. This study demonstrates that children with AIH receiving standard-of-care therapy demonstrate altered growth trajectories, long-term excess weight gain, obesity, and linear growth delay. Young age at diagnosis and >10 mg of daily prednisone at 6 months are predictors for linear growth delay. These data indicate the need to re-evaluate standard treatment algorithms for pediatric AIH in terms of steroid dosing and potential nonsteroid alternatives.